2022
DOI: 10.1039/d1cy02121d
|View full text |Cite
|
Sign up to set email alerts
|

Surface ligands enhance the catalytic activity of supported Au nanoparticles for the aerobic α-oxidation of amines to amides

Abstract: The catalytic aerobic α-oxidation of amines in water is an atom economic and green alternative to current methods of amide synthesis. The reaction uses O2 as terminal oxidant, avoids hazardous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…As a rare example, Beller et al reported a Ru-catalysed α-methylene alkynylation of tertiary amines via β-hydride elimination 44 ; however, the substrate scope was very narrow, and hydrogenation of the products usually occurred as a side reaction. In addition, during the revision of this paper, Slowing et al also reported α-methylene-oxygenation reactions and a few limited examples of α-methylene alkynylation of tertiary amines via β-hydride elimination in the presence of an Au nanoparticle catalyst supported on mesoporous silica with pyridyl groups, while the yields (8-16%) and turnover numbers (2-4) were quite low and insufficient for organic synthetic applications, and the detailed reaction mechanism for the amine oxidation was unrevealed 45 . Quite recently, Schoenebeck and Rovis et al realised regioselective oxidative α-C-H alkylation of tertiary amines at the more-substituted positions by utilising the Curtin-Hammett principle via reversible and fast HAT catalysis; 30 however, in principle, the unique regioselectivity is derived not from the amine oxidation step but from the reaction between amino alkyl radicals and electrophiles, which limits the types of functionalisation to reactions like Giese radical addition, and regioselectivity control between sterically hindered positions (e.g., linear methylene vs cyclic methylene) is quite difficult 30 .…”
mentioning
confidence: 92%
“…As a rare example, Beller et al reported a Ru-catalysed α-methylene alkynylation of tertiary amines via β-hydride elimination 44 ; however, the substrate scope was very narrow, and hydrogenation of the products usually occurred as a side reaction. In addition, during the revision of this paper, Slowing et al also reported α-methylene-oxygenation reactions and a few limited examples of α-methylene alkynylation of tertiary amines via β-hydride elimination in the presence of an Au nanoparticle catalyst supported on mesoporous silica with pyridyl groups, while the yields (8-16%) and turnover numbers (2-4) were quite low and insufficient for organic synthetic applications, and the detailed reaction mechanism for the amine oxidation was unrevealed 45 . Quite recently, Schoenebeck and Rovis et al realised regioselective oxidative α-C-H alkylation of tertiary amines at the more-substituted positions by utilising the Curtin-Hammett principle via reversible and fast HAT catalysis; 30 however, in principle, the unique regioselectivity is derived not from the amine oxidation step but from the reaction between amino alkyl radicals and electrophiles, which limits the types of functionalisation to reactions like Giese radical addition, and regioselectivity control between sterically hindered positions (e.g., linear methylene vs cyclic methylene) is quite difficult 30 .…”
mentioning
confidence: 92%
“…As displayed in Fig. S4,† cationic Au δ + species displaying a higher BE of 84.9 eV are observed to coexist with metallic Au 0 species, 43 and the atomic fraction of Au δ + is calculated to be about 69%. On this reference catalyst, the conversion of vanillyl alcohol can only reach 23% under exactly the same reaction conditions (entry 7), while the selectivity to vanillin remains at 100%.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, organic ligands have been found to directly influence the catalytic behavior of metals through a variety of different mechanisms. Attaching organic ligands to a metal catalyst has been shown to alter the electronic properties of the metal by changing the electron density of the metallic active site. , Ligands can also be used to provide additional functionality at an active site as seen in phosphonic acid-modified supported metal catalysts in which the added Brønsted acidity from the self-assembled monolayer (SAM) can improve hydrodeoxygenation rates, or in the case where an amine can be incorporated into the tail of the SAM, offering additional reactant stabilization during CO 2 reduction . The ligand moiety has been shown to specifically orient reactant molecules through intermolecular hydrophobic interactions or aromatic stacking to greatly improve reaction selectivity, conceptually similar to molecular recognition that is seen in many enzymes .…”
Section: Introductionmentioning
confidence: 99%